Analisis Strategi Jaringan Bisnis, Pemasaran dan Produksi Pada Produk Roll Cake “On a Roll” - Resya Dwi Marselina; Amanda Cahya Nilamsari; Asep Nurjaman; Dede Nurhasanah; Farhan Nur Jamal; Ilham Sandi Ferdiana (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2024)
This research is motivated by an analysis of business networks, marketing and production in the business world which creates very tight competition. To respond to this, the author conducted business network analysis research, marketing and production carried out by the UMKM Roll Cake